Paternal Care Impacts Oxytocin Expression in California Mouse Offspring and Basal Testosterone in Female, but Not Male Pups - Yohn, Christine N.; Leithead, Amanda B.; Ford, Julian; Gill, Alexander; Becker, Elizabeth A. (Frontiers in Behavioral Neuroscience, 2018)
Natural variations in parenting are associated with differences in expression of several hormones and neuropeptides which may mediate lasting effects on offspring development, like regulation of stress reactivity and social behavior. Using the bi-parental California mouse, we have demonstrated that parenting and aggression are programmed, at least in part, by paternal behavior as adult offspring model the degree of parental behavior received in development and are more territorial following high as compared to low levels of care. Development of these behaviors may be driven by transient increases in testosterone following paternal retrievals and increased adult arginine vasopressin immunoreactivity within the bed nucleus of the stria terminalis (BNST) among high-care offspring. It remains unclear, however, whether other neuropeptides, such as oxytocin (OT), which is sensitive to gonadal steroids, are similarly impacted by father-offspring interactions. To test this question, we manipulated paternal care (high and low care) and examined differences in adult offspring OT-ir within social brain areas as well as basal T and corticosterone (Cort) levels. High-care offspring had more OT-ir within the paraventricular nucleus (PVN) and supraoptic nucleus (SON) than low-care offspring. Additionally, T levels were higher among high-care than low-care females, but no differences were found in males. There were no differences in Cort indicating that our brief father-pup separations likely had no consequences on stress reactivity. Together with our previous work, our data suggest that social behavior may be programmed by paternal care through lasting influences on the neuroendocrine system.